Hak-Hak Anak di dalam Lembaga Pembinaan Khusus Anak menurut Hukum Islam: Studi Analisis Pengasuhan Anak di LPKA Kelas I Medan - Siti Aminah; Iwan (Al-fiqh, 2026)
Children in conflict with the law remain children who have the right to be cared for, protected, and loved. When a child is placed in a Special Juvenile Correctional Institution (LPKA), some of the parenting responsibilities that should be carried out by parents are transferred to the state. This study aims to analyze the fulfillment of the rights of children in the Class I A LPKA in Medan from the perspective of Islamic law, specifically the concept of ḥaḍānah, while also examining it within the framework of Indonesian positive law. The study employs an empirical-juridical method using a case study approach through observation and interviews. The children included in this study are those under the age of 17, with the age range observed in the field varying from 10 to 17 years. The results indicate that the fulfillment of basic rights such as food, education, health care, and religious activities is being met; however, parental involvement is not structurally guaranteed. Based on interviews with guidance officers, there are no regulations requiring parents to visit; the institution only provides general visiting hours. This study recommends that the LPKA establish mandatory visiting hours for parents as a form of ongoing parental responsibility (ḥaḍānah).